Systematic Review and Meta-analysis: Changes of Gut Microbiota before and after Menopause. (25th July 2022) - Yang, Meina; Wen, Shu; Zhang, Jing; Peng, Jin; Shen, Xiaoyang; Xu, Liangzhi
Abstract : Objective . To systematically evaluate the differences in intestinal flora before and after menopause. To provide a possible mechanism for perimenopausal syndrome and provide a basis for probiotics as adjuvant therapy. Methods . MEDLINE, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials (CENTRAL), CNKI, Wanfang, and VIP databases were searched. The included studies were case-control studies. Results . Three case-control studies were included, with a total of 156 people. At the phylum level, there were no differences between premenopausal and postmenopausal women. At the genus level, the relative abundances of A. odoratum and B. cholerae were higher in postmenopausal women than in premenopausal women, with no differences among other genera. The Shannon diversity index increased after menopause, but no differences were found. Only one study found a positive association of estradiol with Gammaproteobacteria and Myxococcales and a negative association with Prevotellaceae. Conclusions . On the basis of previous studies, it was found that there was no significant difference at the phylum level between postmenopausal women and premenopausal women, but Odoribacter and Bilophila increased at the genus level in postmenopausal women. The class of Gammaproteobacteria may be positively correlated with estradiol. Limited by the number of included studies, more high-quality clinical studies are needed for validation.